The inter-tier spread of housing bubbles: are luxury markets to blame? - Kuo, Shew-Huei; Lee, Ming-Te; Lee, Ming-Long (International Journal of Strategic Property Management, 2021)
Understanding the spread of asset bubbles is pivotal to the effectiveness of risk management. This study thus estimates housing bubbles and investigates how and to what extent price bubbles spread between the tiers of luxury and mass housing in Hong Kong. The results show that price bubbles spread between housing tiers, the spreading of bubbles is not uni-directional from luxury to mass tiers, and more than 60% of bubbles come from inter-tier spreading. Moreover, bubble shocks from the luxury tier have stronger spreading influences on the movements of bubbles in the mass housing tier than the other way around during the period before the end of the global financial crisis (GFC), whereas the opposite is true for the period after GFC. The findings are important for policy makers attempting to tackle soaring housing bubbles, financial institutions seeking to managing lending risk, and housing investors wanting to time the submarkets.First published online 11 February 2021